Entre, o prescrito, o lido e o possível: novas ideias pedagógicas disseminadas pelos impressos educacionais e suas formas de apropriação no fazer do Grupo Escolar de Ibiá-MG, 1932 a 1946 - Souto, Adilour Nery (2019)
This doctoral thesis is located in the research line of the History and Historiography of Education, it is inserted in the subarea of the History of the Educational Institutions and Pedagogical Principles , and one enters the analysis of the legal interventions, the reforms of primary education in Minas Gerais, with the prescription of the use of printed matter: pedagogical and periodical manuals, as efficient devices in order to put in circulation the proposals of the New School, from 1932 to 1946, in the making of the Ibiá School Group.The time cut corresponds to the year 1932, the year of creation and installation of the Ibiá School Group and the landmark of the Manifesto of the Education Pioneers, and in 1946, the year of renaming the Ibiá School Group, which was renamed the Dom Jose Gaspar School Group .The objective of the research is to understand the system of prescription, circulation and the assimilation of pedagogical ideas from the educational forms as a way of perceiving the tensions in the process of appropriation and reappropriation of the pedagogical theories and of the teaching practices in the daily life of the School Group of Ibiá , within the defined period of study. Our challenge is to perceive the school culture from prescriptions and intra-school relations between pedagogical ideas, as a theory, and the pedagogical practices developed by the different actors: teachers, directors and inspectors, involved in the dynamics between the prescribed, read and the possible from the movement, disseminated by educational forms. Our thesis is between prescribed and performed, for contradictions reveal that ideal New School occurred much more in the realm of ideas than in the s practice. Thus, the research problem is based on the tensions between theories and pedagogical practices and / or teaching practices that gain relevance through the ways in which the school culture is constituted from the Escolanovista movement in the School Groups, specifically in the School Group of Ibiá, in the Triângulo Mineiro. It is a search under the analytical perspective of sources, raised through the articulation of synchronic and diachronic information between the singular and the universal, and the relations of reciprocity and determination between the spheres: national, regional and local. The research has unfolded as bibliographical and documentary research, counted with quantitative and qualitative data obtained in the consultation of documentary and iconographic sources with the use of primary and secondary sources submitted to explanatory analyzes anchored in cultural history.The study seeks to capture the strategies drawn to train and / or prepare teachers, based on theoretical and methodological concepts that supported the most modern methods to be applied in education. We start from the textbooks: Teaching the New School,Alfredo Miguel Aguayo and The technique of modern pedagogy, Everardo Backeuser, these being the main references of readings School Group of teacher Ibiá in the period under study, as well as magazine Teaching, which sought to promote the New School. The results of the research indicate that the pedagogical manuals and the Journal of Teaching helped to stimulate consciously and / or unconsciously in the professionals of this institution a change of mentality in the way of conceiving the child, teaching and knowledge. It is concluded that these forms contributed significantly to the process of pedagogical renewal, even if gradually, in the transition and / or small modifications of the school culture, of the Ibiá School Group.